PENDAMPINGAN WIDYAISWARA DALAM MENUMBUHKAN SELF EFFICACY PESERTA PELATIHAN KEPEMIMPINAN PENGAWAS (PKP) ANGKATAN I TAHUN 2022 DI PPSDM KEMENDAGRI REGIONAL BANDUNG - Tasia Apriani, - (2022)
This research was motivated by the coaching provided by Widyaiswara in developing self efficacy participant of supervisor leadership training (SLT). The purpose of this research is to describe the Widyaiswara coaching of supervisor leadership training (SLT) batch I in 2022, self efficacy of supervisor leadership training (SLT) batch I in 2022, and responce trainee to widyaiswara coaching of supervisor leadership training (SLT) batch I in 2022. The method used is descriptive method with a qualitative approach. The data collection technique used interview techniques, observation, and documentation. The research subjects consisted of 5 people namely is 1 training manager, 2 Widyaiswara, and 2 trainee. Based on the research findings, related to the main widyaiswara coaching in developing self efficacy trainee showed that: 1) the widyaiswara coaching in developing self efficacy tarinee of supervisor leadership tarining (SLT) batch I in 2022 there are several indicators is modelling, mentoring, organizing, and teaching. 2) seen from self efficacy trainee consisting of magnitude, generality, and strength can run smoothly and the trainees can feel the coaching process. 3) responce trainee to Widyaiswara coaching as a form of strengthening success Widyaiswara coaching that can be seen from appearance and Widyaiswara competence. Keywords: Coaching, Widyaiswara, Self Efficacy